2000
DOI: 10.1182/blood.v95.12.3750.012a24_3750_3757
|View full text |Cite
|
Sign up to set email alerts
|

Capture of cytokine-responsive genes (NACA and RBM3) using a gene trap approach

Abstract: We have developed a gene trap approach to select specific cytokine receptor/ligand responsive genes in the cell line TF-1. This cell line exhibits a dependency on granulocyte-macrophage colony-stimulating factor (GM-CSF) or interleukin-3 (IL-3) and responds to interleukin-5 (IL-5). In an attempt to detect genes modulated by one of these factors, cells were infected with the Rosaβgeo retrovirus in the presence of GM-CSF, IL-3, or IL-5 and clones were selected for retroviral integration on the basis of G418 resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…For instance, RNA binding motif protein 3 (RBM3) was ϩ2.4-fold upregulated in response to acute ANG II treatment; RBM3 is a cold-stress-induced RNA binding protein that affects posttranscriptional regulation of gene expression, possibly facilitating translation by binding 18S ribosomal RNA (17). RBM3 is upregulated in response to cytokines and may be associated with tissue growth and differentiation as it is also upregulated in proliferative processes during hematopoesis (6). Also strongly upregulated acutely (ϩ1.7-fold) was angiomotin, a cell-surface protein that transduces angiostatin-induced inhibition of cell motility and induction of apoptosis (65).…”
Section: Acute Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, RNA binding motif protein 3 (RBM3) was ϩ2.4-fold upregulated in response to acute ANG II treatment; RBM3 is a cold-stress-induced RNA binding protein that affects posttranscriptional regulation of gene expression, possibly facilitating translation by binding 18S ribosomal RNA (17). RBM3 is upregulated in response to cytokines and may be associated with tissue growth and differentiation as it is also upregulated in proliferative processes during hematopoesis (6). Also strongly upregulated acutely (ϩ1.7-fold) was angiomotin, a cell-surface protein that transduces angiostatin-induced inhibition of cell motility and induction of apoptosis (65).…”
Section: Acute Responsesmentioning
confidence: 99%
“…As mentioned above, Rho GTPase is an important second messenger system in transducing ANG II effects on heart and other tissues. Integrins play a crucial role in cardiac hypertrophy, linking the ECM to the cytoskeleton and transducing extracellular mechanical stress and chemical signals (6). The significant cellular component GO terms were primarily cytosolic terms for ribosome and microtubules, although there were also significant terms for lysosome and cell-substrate adhesion junctions.…”
Section: Expression Changes Common To Both Acute and Chronic Responsesmentioning
confidence: 99%
“…RBM3 contributes to the response of cellular stressors, such as degenerative and hypoxic conditions (7,14). Moreover, RBM3 has been documented to promote cell proliferation and erythropoietic differentiation (15,16). Recent studies have demonstrated that RBM3 plays a promoting role in human colorectal cancer (17,18) and prostate cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…The retroviral vector ROSA␤EGFP, a gift of Dr. S. Gomez (INSERM U119, Marseille, France), was derived from the ROSA␤geo vector [11,25], and its construction will be described elsewhere (Sophie Gomez and Patrice Dubreuil, unpublished data). Briefly, this vector has a deletion of viral enhancers and a splice acceptor (SA) sequence in front of a promoterless EGFP gene, allowing the production of a chimeric transcript containing at least the ATG of EGFP, from which the EGFP protein expression can be obtained and monitored by fluorescence analysis.…”
Section: Retroviral Vectors and Infectionsmentioning
confidence: 99%
“…In an attempt to isolate M-CSF-responsive genes, we used an in vitro gene trap strategy [11], taking advantage of the retroviral vector ROSA␤EGFP, which places the enhanced green fluorescent protein (EGFP) reporter gene under the control of the regulatory elements of genes disrupted by retroviral insertion. As a model, we used FDC-P1 cells expressing the murine M-CSF-R (FD-Fms cells).…”
Section: Introductionmentioning
confidence: 99%